2013
DOI: 10.4276/030802213x13576469254612
|View full text |Cite
|
Sign up to set email alerts
|

An International Systematic Mapping Review of Educational Approaches and Teaching Methods in Occupational Therapy

Abstract: Introduction: Scholars have long examined educational approaches and teaching methods in occupational therapy, producing a wide range of educational scholarship. Yet the scope of the scholarship has not been systematically categorised and described, leaving the field without a baseline and guide for its educational science.Method: A systematic mapping review identified topics, research designs, levels of impact and themes across educational scholarship. Through comprehensive database searches and inclusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 148 publications
2
37
0
1
Order By: Relevance
“…The need to create more opportunities for students to experience and reflect on what they learn requires educators to be more explicit about how, why, where, and what they teach. Whereas other experiential approaches such as problem-based learning have solid grounding in the occupational therapy literature 15 , approaches that focus on community and technology-rich learning spaces are not well detailed in existing scholarship. Accordingly, student feedback on this course redesign provides encouragement for educators to share how they utilise novel learning spaces and reflective processes in occupational science and occupational therapy programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to create more opportunities for students to experience and reflect on what they learn requires educators to be more explicit about how, why, where, and what they teach. Whereas other experiential approaches such as problem-based learning have solid grounding in the occupational therapy literature 15 , approaches that focus on community and technology-rich learning spaces are not well detailed in existing scholarship. Accordingly, student feedback on this course redesign provides encouragement for educators to share how they utilise novel learning spaces and reflective processes in occupational science and occupational therapy programmes.…”
Section: Discussionmentioning
confidence: 99%
“…I received the Fellowship in March 2012 and began the second phase of my course redesign in the subsequent summer. The limited occupational therapy scholarship on teaching and learning [15][16][17] offered little guidance for this aspect of the course redesign, but it did suggest that new instructional designs 18 related to online technologies 13,19 and synchronous student collaborations 20 showed promise, especially when coupled with structured reflection 20 . (More recent examples of technology-based international occupational therapy educational collaborations 21 were not published when I undertook the course redesign.)…”
Section: Redesign #2: Incorporate Global Perspectives Via Synchronousmentioning
confidence: 99%
“…This focus on efficacy is likely in response to gaps recently identified in education research (e.g., Hooper et al, 2013). Moreover, recognizing that occupational therapy education research is in an early phase of development, clearly studies with appropriate data collection, rigorous analysis, and broad outcomes are necessary.…”
Section: Resultsmentioning
confidence: 99%
“…In occupational therapy, systematic mapping studies have found that academic and fieldwork education research is characterized by descriptive inquiry methods used to study learning activities in local contexts, where student perceptions are the primary outcomes; however, studies frequently omit theoretical frameworks and use of philosophy, history, and theory as windows on data (Hooper, King, Wood, Bilics, & Gupta, 2013;Roberts, Hooper, Wood, & King, 2014). While much of the work in occupational therapy education research can be classified as descriptive, it is not as if it has been intentionally and systematically descriptive.…”
Section: The Lack Of Philosophical Historical and Theoretical Inquimentioning
confidence: 99%
“…Experts recognize that clinical reasoning is an essential skill for practice (Furze et al, 2015;McCannon, Robertson, Caldwell, Juwah, & Elfessi, 2004;Scaffa & Wooster, 2004), and that occupational therapy education is initially responsible for the development and growth of this critical skill (Coker, 2010;Scaffa & Smith, 2004). However, there is little evidence about which instructional methods are best for, or unique to, occupational therapy education (Hooper, King, Wood, Bilics, & Gupta, 2013).…”
Section: Introductionmentioning
confidence: 99%